Variabilidade temporal e meridional de estimativas de Satélite da concentração de clorofila superficial na plataforma continental brasileira - Ciotti, Áurea M. [UNESP]; Garcia, Carlos A.E.; Jorge, Daniel S.F. [UNESP] (My University, 2010)
Forecast of biological consequences of climate changes depend on both long-term observations and the establishment of carbon budgets within pelagic ecosystems, including the assessment of biomasses and activities of all players in the global carbon cycle. Approximately 25% of oceanic primary happen over continental shelves, so these are important sites for studies of global carbon dynamics. The Brazilian Continental Shelf (BCS) has sparse and non-systematic in situ information on phytoplankton biomass, making products derived from ocean color remote sensing extremely valuable. This work analyzes chlorophyll concentration (Chl) estimated from four ocean color sensors (CZCS, OCTS, SeaWiFS and MODIS) over the BCS, to compare Chl and annual cycles meridionally. Also, useful complementary ocean color variables are presented. Chl gradients increased from the central region towards north and south, limited by estuarine plumes of Amazon and La Plata rivers, and clear annual Chl cycles appear in most areas. In southern and central areas, annual cycles show strong seasonal variability while interannual and long-term variability are equally important in the remaining areas. This is the first comparative evaluation of the Chl over the BCS and will aid the understanding of its long-term variability; essential initial step for discussions of climate changes.
Temporal and meridional variability of Satellite-estimates of surface chlorophyll concentration over the Brazilian continental shelf
Keywords: Annual variability; CDOM index; Chlorophyll concentration; Fluorescence line height; Ocean color remote sensing; South West Atlantic